A Comprehensive Approach to PROMs in Elective Orthopedic Surgery : Comparing Effect Sizes across Patient Subgroups - Äärimaa, Ville; Kohtala, Karita; Rantalaiho, Ida; Ekman, Elina; Mäkelä, Keijo; Taskinen, Hanna-Stiina; Ryösä, Anssi; Kostensalo, Joel; Meronen, Saara; Laaksonen, Inari (MPDI, 2025)
Background: There is limited knowledge regarding the comparative patient-reported outcomes (PROMs) and effect sizes (ESs) across orthopedic elective surgery.
Methods: All patient data between January 2020 and December 2022 were collected, and treatment outcomes assessed as a PROM difference between baseline and one-year follow-up. The cohort was divided into subgroups (hand, elbow, shoulder, spine, hip, knee, and foot/ankle). The PROM ESs were calculated for each patient separately, and patients with ES > 0.5 were considered responders.
Results: In total, 7695 patients were operated on. The mean ES across all patient groups was 1.81 (SD 1.41), and the largest ES was observed in shoulder patients and the smallest in hand patients. Overall, shoulder, hip, and knee patients had a larger ES compared to hand, spine, and foot/ankle patients (p < 0.0001). The proportion of positive responders ranged between 91-94% in the knee, shoulder, and hip, and 69-70% in the hand, spine, and foot/ankle subgroups.
Conclusions: The ESs are generally high throughout elective orthopedic surgery. However, based on our institutional observations, shoulder, hip, and knee patients experience larger treatment effects compared to hand, spine, and foot/ankle patients, among whom there are also more non-responders. The expected treatment outcomes should be clearly communicated to patients when considering elective surgery. Because of the study limitations, the results should be approached with some caution.